IMPORTANCIA DE LA EDUCACIÓN PÚBLICA EN LA CONSTITUCIÓN DE LAS CLASES MEDIAS ECUATORIANAS ENTRE LA REVOLUCIÓN LIBERAL Y 1970 - Moreno, Kintia (2024)
The following paper inquires how che public university, as a homogenizing and "civilizing" instrument of the state, has influenced the constitution of Ecuadorian middle classes beween the period of the Liberal Revolution and 1970. The importante of public universities with regards to professional training is problematized. These professionals are an importat group in the consolidation of a middle class in Ecuador. The paper presents a portrait of significant historical and political events that have marked the transformations experienced by the university such as the creation of new universities, schools, departments, and the degree they offer. Particular attention is paid to social struggles for open and universal access to public universities which marks a milestone in the democratization of higher education. However we cannot lose sight of the different levels of inclusion that popular and working-classes have experienced within university life, even if they are still scarce.